Binocular benefit following monocular subretinal AAV injection in a mouse model of autosomal dominant retinitis pigmentosa (adRP). (May 2023) - Ahmed, Chulbul M.; Massengill, Michael T.; Ildefonso, Cristhian J.; Jalligampala, Archana; Zhu, Ping; Li, Hong; Patel, Anil P.; McCall, Maureen A.; Lewin, Alfred S.
Graphical abstract: Treatment of one eye with an RNA replacement vector (AAV-RHO820-shRNA820) preserves retinal structure and function in both the injected and naive eyes of a transgenic mouse model of P23H RHO adRP. Abstract: Autosomal dominant retinitis pigmentosa (adRP) is frequently caused by mutations in RHO, the gene for rhodopsin. In previous experiments in dogs with the T4R mutation in RHO, an AAV2/5 vector expressing an shRNA directed to human and dog RHO mRNA and an shRNA-resistant human RHO cDNA (AAV- RHO820-shRNA820 ) prevented retinal degeneration for more than eight months following injection. It is crucial, however, to determine if this RNA replacement vector acts in a mutation-independent and species-independent manner. We, therefore, injected mice transgenic for human P23H RHO with this vector unilaterally at postnatal day 30. We monitored their retinal structure by using spectral-domain optical coherence tomography (SD-OCT) and retinal function using electroretinography (ERG) for nine months. We compared these to P23H RHO transgenic mice injected unilaterally with a control vector. Though retinas continued to thin over time, compared to control injected eyes, treatment with AAV-RHO820-shRNA820 slowed the loss of photoreceptor cells and the decrease in ERG amplitudes during the nine-month study period. Unexpectedly, we also observed the preservation of retinal structure and function in the untreated contralateral eyes of AAV- RHO820-shRNA820 treated mice. PCR analysis and western blots showed that a low amount of vector from injected eyes was present in uninjected eyes. In addition, protective neurotrophic factors bFGF and GDNF were elevated in both eyes of treated mice. Our finding suggests that using this or similar RNA replacement vectors in human gene therapy may provide clinical benefit to both eyes of patients with adRP.